(untitled) (MAUSAM, 2026)
Evapotranspiration (ET) is the primary process of water transfer in the hydrological cycle over land and is linked to water, energy and carbon cycles. While the global hydrological cycle is expected to intensify in a warming climate with enhanced ET and precipitation, the magnitude and spatial distribution of regional scale response of ET to climate change remains uncertain. Here we present an analysis of in-situ observations of ET from 23 stations in India during 1979-2008, which shows that the annual ET has declined by about 9% over the humid sub-regions of the Indo-Gangetic Plain (IGP). Additional analysis from high-resolution climate model simulations and observed climate datasets lend support to the role of aerosol-induced solar-dimming in intensifying ET reductions, in a background of decreasing monsoon precipitation and soil-moisture levels, over the IGP